M1 and M2 macrophage proteolytic and angiogenic profile analysis in atherosclerotic patients reveals a distinctive profile in type 2 diabetes. (July 2015) - Roma-Lavisse, Charlotte; Tagzirt, Madjid; Zawadzki, Christophe; Lorenzi, Rodrigo; Vincentelli, André; Haulon, Stephan; Juthier, Francis; Rauch, Antoine; Corseaux, Delphine; Staels, Bart; Jude, Brigitte; Van Belle, Eric; et al.
This study aimed to investigate atherosclerotic mediators' expression levels in M1 and M2 macrophages and to focus on the influence of diabetes on M1/M2 profiles. Macrophages from 36 atherosclerotic patients (19 diabetics and 17 non-diabetics) were cultured with interleukin-1β (IL-1β) or IL-4 to induce M1 or M2 phenotype, respectively. The atherosclerotic mediators' expression was evaluated by quantitative reverse transcription-polymerase chain reaction (RT-PCR). The results showed that M1 and M2 macrophages differentially expressed mediators involved in proteolysis and angiogenesis processes. The proteolytic balance (matrix metalloproteinase-9 (MMP-9)/tissue inhibitor of metalloproteinase-1 (TIMP-1), MMP-9/plasminogen activator inhibitor-1 (PAI-1) and MMP-9/tissue factor pathway inhibitor-2 (TFPI-2) ratios) was higher in M1 versus M2, whereas M2 macrophages presented higher angiogenesis properties (increased vascular endothelial growth factor/TFPI-2 and tissue factor/TFPI-2 ratios). Moreover, M1 macrophages from diabetics displayed more important proangiogenic and proteolytic activities than non-diabetics. This study reveals that M1 and M2 macrophages could differentially modulate major atherosclerosis-related pathological processes. Moreover, M1 macrophages from diabetics display a deleterious phenotype that could explain the higher plaque vulnerability observed in these subjects.